Hagiograficzny klucz nowej ewangelizacji - Kochel, Jan (Studia Pastoralne, 2026)
The author of the article points to a hagiographic key for interpretation of a programme for a new evangelism. An analysis of the idea ‘communion of saints’ has aided in his discovery, focusing attention on a new approach (hagiographic) in the interpretation of the Bible and centering on the saints as icons of the new evangelism. The saints show the way for effective realisation of the program for a new evangelism, for which confirmation we have no further to look than the statements of Benedict XVI and Francis. The saints become the real protagonists of the new evangelism and challenge us to follow their lives and mission in the Church. This appeal is a challenge for contemporary pastors, catechists and teachers to reach for the personal examples of the saints and the blessed of the Church in teaching and their intercession for the realisation of sharing the faith.